2020
DOI: 10.22159/ajpcr.2020.v13i8.38357
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Antiparasitic Drug Ivermectin for Various Viral Infections and Possibilities of Using It for Novel Severe Acute Respiratory Syndrome Coronavirus 2: New Hope to Treat Coronavirus Disease-2019

Abstract: The novel coronavirus infection has spread all over the world. With no specific drug or vaccine, the process of “drug repurposing” becomes a feasible solution. As severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has 80% sequence similarity with the SARS-CoV, the nuclear import inhibitor “Ivermectin” (IVM) has recently been studied as a possible treatment option for coronavirus disease-2019 (COVID-19). The article aims to provide a review on structure and immunogenicity of SARS-CoV-2, indications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recent studies that examined the efficacy of Ivermectin have shown antiviral activity for many viral infections (Jabeen et al, 2020). A retrospective analysis of consecutive patients with COVID-19 from four hospitals in Florida, USA, compared 173 patients who received Ivermectin plus Hydroxychloroquine, or Hydroxychloroquine with Azithromycin, versus 103 patients who received usual care plus Hydroxychloroquine, or Hydroxychloroquine with Azithromycin.…”
Section: Type Of Treatmentmentioning
confidence: 99%
“…Recent studies that examined the efficacy of Ivermectin have shown antiviral activity for many viral infections (Jabeen et al, 2020). A retrospective analysis of consecutive patients with COVID-19 from four hospitals in Florida, USA, compared 173 patients who received Ivermectin plus Hydroxychloroquine, or Hydroxychloroquine with Azithromycin, versus 103 patients who received usual care plus Hydroxychloroquine, or Hydroxychloroquine with Azithromycin.…”
Section: Type Of Treatmentmentioning
confidence: 99%
“…An in vitro study reported that ivermectin inhibits SARS-CoV-2, with a single addition to Vero/hSLAM cells 2-h post infection and reduces viral RNA ~5000- at 48 h. 2 , 3 , 10 , 11 , 26 , 27 Recent studies that examined the efficacy of ivermectin have shown antiviral activity for many viral infections. 28 …”
Section: Discussionmentioning
confidence: 99%
“…In present scenario, this drug is also useful in the management of SARS-COV-2. 9,10 The available literature studies describe utilization of few analytical methods for the evaluation of ivermectin in tablet dosage form. These methods are based on various techniques such as Ultra Violet spectroscopy, diffused reflectance spectroscopy, HPTLC, HPLC with Tandem mass spectroscopy and RP-HPLC.…”
Section: Introductionmentioning
confidence: 99%